Peran Wanita Dalam Sains Dan Technology - Wati, Rifki Elinda; Adam, Adiyana (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2022)
There is a connection in social life regarding the use of science and technology and this of course involves both women and men.In social life, it is often the roles of women and men.When we talk about the problems of science and technology.This of course will trigger a gap.Women's access to science and technology is still constrained by gender inequality.This is due to the role of many women as users of science and technology products, not as creators.This is especially the case for women in developing countries.Developing countries are fields that foster inequality between men and women in access to science and technology.This is due to the lower education level of women than men.